Review and Assessment of Crop-Related Digital Tools for Agroecology - Anastasiou, Evangelos; Kasimati, Aikaterini; Papadopoulos, George; Vatsanidou, Anna; Gemtou, Marilena; Kantelhardt, Jochen; Gabriel, Andreas; Schwierz, Friederike; Matavel, Custodio Efraim; Meyer-Aurich, Andreas; Maritan, Elias; Behrendt, Karl; et al. (MDPI, 2025)
The use of digital tools in agroecological crop production can help mitigate current farming challenges such as labour shortage and climate change. The aim of this study was to map digital tools used in crop production, assess their impacts across economic, environmental, and social dimensions, and determine their potential as enablers of agroecology. A systematic search and screening process, following the Preferred Reporting Items for Systematic reviews and Meta-Analyses methodology, identified 453 relevant studies. The results showed that most digital tools are applied for crop monitoring (83.4%), with unmanned aerial vehicles (37.7%) and camera sensors (75.2% combined) being the most frequently used technologies. Farm Management Information Systems (57.6%) and Decision Support Systems (25.2%) dominated the tool categories, while platforms for market access, social networking, and collaborative learning were rare. Most tools addressed the first tier of agroecology, which refers to input reduction, highlighting a strong focus on efficiency improvements rather than systemic redesign. Although digital tools demonstrated positive contributions to social, environmental, and economic dimensions, studies concentrated mainly on economic benefits. Future research should investigate the potential role of digital technologies in advancing higher tiers of agroecology, emphasising participatory design, agroecosystem services, and broader coverage of the agricultural value chain.
Keywords: crop production; tiers of agroecology; digitalization; systematic map; smart farming